Mycotic Pulmonary Arterial Aneurysms in an Intravenous Drug User - Laura McLean; Sat Sharma; Bruce Maycher (Canadian Respiratory Journal)
A case of mycotic pulmonary artery aneurysm (PAA) in an intravenous drug user in whom resolution occurred with conservative therapy is described. The natural history of PAA is not well described in the literature. Although PAA is potentially fatal, resolution may occur in patients who do not have hemoptysis. Clinical presentation, diagnosis and management of PAA are reviewed.